Exploring the paradoxical national projection in small and secluded island realities: The case of the Canary Islands - Montesdeoca Pérez, Jorge Antonio (Journal of marine and island cultures, 2024)
This study explores the paradox of nationalism in small insular communities isolated in seas, particularly oceans. Despite their distinct identity, unique history, exclusive connection between people and territory, and strong association between local symbology and landscape, these communities often resist attaining national status, perceiving it as a precursor to statehood. This paradox manifests as an internal conflict between embracing and rejecting a national image. Historically, this resistance has prevailed, subtly shaping the political and social development of such islands. The Canary Islands serve as a prime example of this dynamic. While the archipelago is not currently pursuing nationhood, it presents a unique case for studying nationalism within these insular contexts, with evidence of this paradox in both historical and recent times. Therefore, this article argues for maintaining the scope of nationalism studies within these insular contexts, regardless of whether the communities have become nations. More specifically, this article demonstrates that owing to their interaction with paradox, it can be very beneficial to analyse such insular contexts using established theories that focus on explaining the nation-formation process.